The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/qad.0b013e32834404a1
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal-proB-type natriuretic peptide predicts cardiovascular disease events in HIV-infected patients

Abstract: Background Cardiovascular disease (CVD) is increasing in HIV-infected patients. N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a significant predictor of CVD in the general population. We aimed to quantify the risk of CVD events associated with NT-proBNP at baseline in the Strategies for Management of Anti-Retroviral Therapy study. Methods In a nested case–control study, NT-proBNP was measured at baseline in 186 patients who experienced a CVD event over an average of 2.8 years of follow-up and in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…The biomarkers included: ST2 (fibrosis); GDF-15 (apoptosis); NT-proBNP (myocyte stretch); hsTnI (myocardial injury); hsCRP and IL-6 (inflammation); Cystatin C (renal dysfunction); and D-dimer (thrombosis). (4, 5, 912) Thresholds of risk for ST2, GDF-15, and NT-proBNP were pre-defined based on prior studies associating values exceeding these cut-points with CVD. These thresholds were: ST2 >35 ng/ml, GDF-15 >1200 pg/ml, and NT-proBNP >300 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The biomarkers included: ST2 (fibrosis); GDF-15 (apoptosis); NT-proBNP (myocyte stretch); hsTnI (myocardial injury); hsCRP and IL-6 (inflammation); Cystatin C (renal dysfunction); and D-dimer (thrombosis). (4, 5, 912) Thresholds of risk for ST2, GDF-15, and NT-proBNP were pre-defined based on prior studies associating values exceeding these cut-points with CVD. These thresholds were: ST2 >35 ng/ml, GDF-15 >1200 pg/ml, and NT-proBNP >300 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, measurements were not conducted specifically to detect subclinical vascular disease, but studies such as the one mentioned advocate the use of NTproBNP as a surrogate marker of vascular disease. Duprez et al [14] reported a higher risk of cardiovascular events among patients with HIV infection and higher levels of NT-proBNP than among those with lower levels. This relationship was controlled using traditional cardiovascular risk factors and other biomarkers such as highly sensitive C-reactive protein and D-dimer.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a risk marker of vascular events in the general population [13] and also in patients with HIV infection [14].…”
Section: Introductionmentioning
confidence: 99%
“…Their role in predicting CVD in the HIV-infected population remains unclear [81,83]. Several other biomarkers are currently being evaluated (e.g., markers of thrombotic activity such as d-dimer and fibrinogen, as well as NT-proBNP, which showed an independent association with CVD in an HIV-infected population) [84][85][86]. A biomarker that is new to HIV is sCD163, which has recently been shown to decrease to normal levels after initiation of cART in patients with early HIV, but remains elevated in chronic HIV [87]; results that correspond well to previous endothelial biomarker findings made by others [12].…”
Section: Biomarkers Of Early Atherosclerosismentioning
confidence: 98%